Hypertonic anti-fouling agent and application thereof in water resistance, fouling resistance and oil resistance of fabric
Patent Information
- Application Number
- CN202411419619.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
Existing fabric treatment technology cannot effectively prevent waterproof, stain-proof and oil-proof for a long time, and affects the breathability and feel of the fabric, and cannot meet the special protection needs of traditional fabrics such as intangible cultural heritage embroidery works and Hanfu fabrics.
The preparation method of high-osmotic antifouling agent is adopted, including glycidyl methacrylate, 3-perfluorooctyl 2-acrylate, fluoromethoxysilane compounds, silane coupling agents and nanosilica components. , a protective film or protective layer is formed by stirring and mixing, spray or coated on the fabric.
It significantly improves the waterproof, stain-proof and oil-proof properties of the fabric, maintains breathability and feel, provides long-term protection, extends the service life of the fabric, and is suitable for the protection of traditional fabrics.
Smart Images

Figure CN119308148A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric treatment, and in particular to a high-osmotic antifouling agent and application thereof in fabrics for waterproofing, antifouling and oil resistance. Background Art
[0002] As modern society's awareness of quality of life and environmental protection continues to improve, people's demand for fabric functionality is also gradually increasing, especially for traditional fabrics such as intangible cultural heritage embroidery works and Hanfu fabrics. At present, fabric treatment technologies mainly include surface coatings, chemical treatments, and functional additives. Common waterproof, anti-fouling, and oil-proof treatment agents include silane substances, polyurethane resins, etc. These treatment agents improve the waterproof, anti-fouling, and oil-proof properties of fabrics by forming a protective film on the surface of the fabric or forming a protective layer in the fabric fibers.
[0003] Although the existing technology can provide fabrics with waterproof, anti-fouling and oil-proof functions to a certain extent, it still has the following shortcomings: the waterproof, anti-fouling and oil-proof effects of some treatment agents gradually weaken over time and require regular maintenance or re-treatment, which increases the cost and workload of use. After the fabric is treated, its original breathability and feel may be affected, and the comfort and aesthetics of the fabric may be reduced, which does not meet the needs of users. Regarding the protection needs of traditional fabrics such as intangible cultural heritage embroidery works and Hanfu fabrics, the existing technology may not be able to meet their special functional requirements, such as protecting the embroidery patterns on the fabric or improving the anti-fouling ability of Hanfu fabrics.
[0004] The limitations of the above existing technologies restrict the further development and application of fabric treatment technology. In particular, for the protection needs of traditional fabrics, the existing technologies cannot provide solutions that meet their special needs, resulting in the limitation of the technical development in the field of fabric protection. Therefore, it is necessary to propose a new type of high-penetration antifouling agent that can effectively solve the problems of the existing technology, meet the protection needs of traditional fabrics, and improve the functionality and environmental friendliness of fabrics. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a hypertonic antifouling agent and its application in fabrics for waterproofing, antifouling and oil resistance. The present invention is particularly suitable for the protection of intangible cultural heritage embroidery works, Hanfu fabrics, etc., and is waterproof, antifouling and oil-proof.
[0006] The technical solution of the present invention is as follows:
[0007] A hyperosmotic antifouling agent is prepared by the following method:
[0008] Glycidyl methacrylate, 3-perfluorooctyl 2-hydroxypropyl acrylate, fluoromethoxysilane compound, initiator, silane coupling agent KH-550 and ethanol are stirred;
[0009] Then mix with nano-silica, water, acrylic resin and ethanol.
[0010] Preferably, a hyperosmotic antifouling agent is prepared by the following method:
[0011] Glycidyl methacrylate, 3-perfluorooctyl 2-hydroxypropyl acrylate, fluoromethoxysilane compound, azobisisobutyronitrile, silane coupling agent KH-550 and ethanol are stirred;
[0012] Then mix with nano-silica, water, acrylic resin and ethanol.
[0013] Preferably, the fluoromethoxysilane compound is trimethoxy(3,3,3-trifluoropropyl)silane and / or 3,3,3-trifluoropropylmethyldimethoxysilane.
[0014] Preferably, a hyperosmotic antifouling agent is prepared by the following method:
[0015] 5-15 parts by weight of glycidyl methacrylate, 10-30 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 5-12 parts by weight of fluoromethoxysilane compound, 0.05-0.9 parts by weight of azobisisobutyronitrile, 1-9 parts by weight of silane coupling agent KH-550 and 100-700 parts by weight of ethanol are stirred;
[0016] The mixture is then mixed with 10-50 parts by weight of nano silicon dioxide, 100-500 parts by weight of water, 100-500 parts by weight of acrylic resin and 500-2000 parts by weight of ethanol.
[0017] Preferably, a hyperosmotic antifouling agent is prepared by the following method:
[0018] 5-15 parts by weight of glycidyl methacrylate, 15-25 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 6-10 parts by weight of fluoromethoxysilane compound, 0.1-0.6 parts by weight of azobisisobutyronitrile, 3-7 parts by weight of silane coupling agent KH-550 and 100-500 parts by weight of ethanol are stirred;
[0019] The mixture is then mixed with 15-35 parts by weight of nano silicon dioxide, 200-400 parts by weight of water, 200-400 parts by weight of acrylic resin and 800-1400 parts by weight of ethanol.
[0020] Preferably, a hyperosmotic antifouling agent is prepared by the following method:
[0021] Add 5-15 parts by weight of glycidyl methacrylate, 15-25 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 6-10 parts by weight of fluoromethoxysilane compound, and 0.1-0.6 parts by weight of azobisisobutyronitrile to 100-500 parts by weight of ethanol, and stir at 55-70° C. for 4-8 hours at a stirring speed of 100-500 rpm under a nitrogen atmosphere;
[0022] Add 3-7 parts by weight of silane coupling agent KH-550, continue stirring at 35-50°C for 2-6 hours, and the stirring speed is 100-500rpm;
[0023] The mixture is cooled to room temperature, and then 15-35 parts by weight of nano-silicon dioxide, 200-400 parts by weight of water, 200-400 parts by weight of acrylic resin and 800-1400 parts by weight of ethanol are added, and the mixture is stirred and mixed evenly.
[0024] The invention also provides an application of a high-osmotic antifouling agent in fabrics for waterproofing, antifouling and oil resistance.
[0025] Preferably, the fabric is silk fabric, embroidery fabric, cotton fabric, polyester fabric, nylon fabric, flannel or chiffon fabric.
[0026] Preferably, the fabric is silk fabric or embroidery fabric.
[0027] Preferably, the use of a hyperosmotic antifouling agent in fabrics for waterproofing, antifouling and oil resistance comprises uniformly applying the hyperosmotic antifouling agent on the fabrics by spraying or coating.
[0028] The hypertonic antifouling agent provided by the present invention has many functions. First, it can form a protective film on the surface of the fabric or form a protective layer in the fiber, effectively improving the waterproofness, antifouling and oil resistance of the fabric, thereby effectively preventing liquid penetration and stain adsorption, and protecting the fabric from water, oil and stains. Secondly, the hypertonic antifouling agent can maintain the air permeability and feel of the fabric, does not affect the comfort and aesthetics of the fabric, and keeps the fabric The original quality and characteristics. In addition, the antifouling agent can also provide a long-term protective effect and extend the service life of the fabric. In general, the hypertonic antifouling agent provided by the present invention has multiple advantages in protecting fabrics, and is particularly suitable for protecting traditional fabrics such as intangible cultural heritage embroidery works and Hanfu fabrics, providing them with a reliable, durable and environmentally friendly protection solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a waterproof test diagram of Example 1 after the high permeability antifouling agent is applied to a dark-colored fabric;
[0031] Figure 2 This is a soy sauce proof test diagram of Example 1 after the hyperosmotic antifouling agent is applied to yellow fabric;
[0032] Figure 3 This is a waterproof test diagram of Example 1 after the high permeability antifouling agent is coated on the silk fabric;
[0033] Figure 4 This is a waterproof test diagram of Example 1 after the high permeability antifouling agent is applied to the embroidery fabric;
[0034] Figure 5 This is a waterproofing experiment diagram of Example 1 after the hyperosmotic antifouling agent is applied to the intangible cultural heritage embroidery artwork;
[0035] Figure 6 This is a comparison chart of pure cotton fabric before and after waterproof treatment. DETAILED DESCRIPTION
[0036] The content of the present invention can be more easily understood by selecting the following detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definition in this specification shall prevail.
[0037] A hyperosmotic antifouling agent is prepared by the following method:
[0038] 5-15 parts by weight of glycidyl methacrylate, 15-25 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 6-10 parts by weight of fluoromethoxysilane compound, and 0.1-0.6 parts by weight of azobisisobutyronitrile are added to 100-500 parts by weight of ethanol, and stirred at 55-70° C. for 4-8 hours at a stirring speed of 100-500 rpm under a nitrogen atmosphere; the fluoromethoxysilane compound is trimethoxy (3,3,3-trifluoropropyl) silane and / or 3,3,3-trifluoropropyl methyldimethoxysilane;
[0039] Add 3-7 parts by weight of silane coupling agent KH-550, continue stirring at 35-50°C for 2-6 hours, and the stirring speed is 100-500rpm;
[0040] After cooling to room temperature, 15-35 parts by weight of nano silicon dioxide, 200-400 parts by weight of water, 200-400 parts by weight of acrylic resin and 800-1400 parts by weight of ethanol are added, and the mixture is stirred and mixed uniformly to obtain the high permeability antifouling agent of the present invention.
[0041] Glycidyl methacrylate, CAS No. 106-91-2, is used as a crosslinking agent and can react with other monomers to form a polymer network structure, thereby enhancing the mechanical strength and water resistance of the final product.
[0042] 3-Perfluorooctyl 2-hydroxypropyl acrylate, 3-(perfluorooctyl)-2-hydroxypropylacrylate. CAS No.: 76962-34-0, 3-Perfluorooctyl 2-hydroxypropyl acrylate has the basic structure of acrylate, that is, it contains an unsaturated double bond -C=C- derived from acrylic acid, which can participate in the formation of the polymer network through a typical free radical polymerization mechanism. In addition, the perfluorooctyl part contains a large number of fluorine atoms, which have very strong hydrophobicity and oleophobicity. Due to the strength and chemical stability of the CF bond, it provides excellent chemical resistance and environmental stability. The hydroxyl -OH at the end of the molecule provides an active site that can participate in further chemical reactions, react with crosslinkers or other functional monomers, and enhance the performance of the final polymer. The introduction of perfluorooctyl significantly improves the overall hydrophobicity of the molecule. Perfluorinated compounds naturally repel water molecules, so when these monomers are integrated into the polymer network, the waterproofness of the overall coating can be significantly improved. The perfluorocarbon chain also exhibits a high degree of repellency to oils and many organic pollutants. In coating applications, this property helps prevent the adsorption and penetration of grease and other contaminants, thereby keeping the coating clean and looking great. Perfluorinated compounds also help reduce the adhesion of dust and particles to the surface, which would normally accumulate without this protection, causing degradation of color and gloss.
[0043] The fluoromethoxysilane compound is trimethoxy (3,3,3-trifluoropropyl) silane and / or 3,3,3-trifluoropropyl methyl dimethoxy silane. 3,3,3-Trifluoropropyl methyl dimethoxy silane, Dimethoxy (methy l) (3,3,3-trifluoropropyl) silane, CAS number: 358-67-8. It provides silane groups, enhances the surface properties of the material, improves adhesion and chemical stability. At the same time, the trifluoropropyl group increases hydrophobicity. Trimethoxy (3,3,3-trifluoropropyl) silane, 3,3,3-trifluoropropyltrimethoxysilane, CAS number: 429-60-7, is a silane compound containing methoxy and trifluoropropyl groups, and its main function is to provide silane groups, thereby improving the surface properties of the material, enhancing its adhesion and chemical stability. At the same time, the presence of the trifluoropropyl group makes the compound hydrophobic, which helps the waterproof and anti-fouling properties of the material surface. Most preferably, the fluoromethoxysilane compound is a mixture of trimethoxy (3,3,3-trifluoropropyl) silane and 3,3,3-trifluoropropylmethyldimethoxysilane, with a mass ratio of 1: (0.3-3).
[0044] Silane coupling agent KH-550 provides amino and silane groups, which help improve adhesion and functionality, and can chemically react with many types of surfaces to enhance interfacial compatibility.
[0045] Azobisisobutyronitrile, as an initiator, can effectively generate free radicals to start the polymerization reaction of monomers containing acrylic acid groups.
[0046] Nano-silicon dioxide, as a matting agent, reduces the gloss of the coating and improves anti-pollution performance. Specifically, nano-silicon dioxide with a particle size of 50nm is used.
[0047] Acrylic resin is water-based, environmentally friendly, and used to improve film-forming properties. CA 7160A acrylic emulsion.
[0048] Specific application of the high permeability antifouling agent of the present invention in waterproof, antifouling and oil-proof fabrics:
[0049] The fabric must be clean, dry, free of coating and oil;
[0050] Spray or apply the high-permeability antifouling agent evenly on the fabric, allow the high-permeability antifouling agent to be fully absorbed on the surface, and let it stand for 10-120 minutes;
[0051] Allow the fabric coated with the high-penetration antifouling agent to air dry naturally for 24 hours.
[0052] The high-osmotic antifouling agent of the present invention has good permeability and strong adhesion, can penetrate into the pores of stone, ceramic tile, wood, cloth and the like, has long-lasting wear resistance, pressure resistance and toughness, strong air permeability, no film, maintains the natural characteristics of stone, ceramic tile, wood and cloth, gives wood excellent anti-corrosion, waterproof, anti-fouling, oil-proof, alkali-proof and acid-proof properties, can effectively control the moisture content of stone and wood, can effectively resist the destructive power and pollution source of alkaline, acid, water media, freeze-thaw wet cycle when used on stone ceramic tile, can make the surface resistant to dirt, easy to clean and maintain, long-lasting, good weather resistance, and effective period of more than 10 years when used on cloth. After curing, the high-osmotic antifouling agent is non-toxic and tasteless, and harmless to the human body.
[0053] In the fields of silk fabrics and embroidery fabrics, the protection and anti-fouling requirements of fabrics are particularly important. Silk fabrics are favored by consumers for their soft, comfortable and breathable characteristics. However, their weak anti-fouling ability and vulnerable characteristics make silk fabrics vulnerable to pollutants such as liquids and grease, thereby affecting their appearance and service life. As an important form of expression of traditional culture, embroidery fabrics also face challenges in protecting the clarity and aesthetics of embroidery patterns, especially in daily use. The hypertonic antifouling agent provided by the present invention has significant advantages in view of the special needs of silk fabrics and embroidery fabrics. By forming a lasting protective film on the surface of the fabric or forming a protective layer between fibers, the hypertonic antifouling agent can effectively prevent the penetration of moisture, dirt and grease, improve the waterproof, antifouling and oil-proof capabilities of the fabric, thereby keeping the fabric clean and beautiful. Compared with traditional treatment methods, the hypertonic antifouling agent of the present invention is not only durable, does not require frequent maintenance or reprocessing, but also does not affect the air permeability and feel of the fabric, ensuring the comfort and aesthetics of the fabric. Therefore, after using the hyperosmotic antifouling agent provided by the present invention, traditional fabrics such as silk fabrics and embroidery fabrics can better maintain their original texture and appearance, extend their service life, and meet consumers' demands for quality and aesthetics.
[0054] In addition to silk fabrics and embroidery fabrics, the hyperosmotic antifouling agent provided by the present invention is also applicable to a variety of other fabrics, including but not limited to cotton, polyester fabrics, nylon fabrics, flannel and chiffon fabrics. These fabrics are widely used in daily life and industrial production, and have different characteristics and uses. By using the hyperosmotic antifouling agent provided by the present invention, these fabrics can be effectively protected, their service life can be extended, and their waterproof, antifouling and oil-proof properties can be improved, thereby meeting people's protection needs for various fabrics and improving their functionality and environmental friendliness.
[0055] Embodiment 1:
[0056] A preparation method of a hyperosmotic antifouling agent:
[0057] 10 g of glycidyl methacrylate, 19.3 g of 3-perfluorooctyl 2-hydroxypropyl acrylate, 8.4 g of 3,3,3-trifluoropropylmethyldimethoxysilane, and 0.2 g of azobisisobutyronitrile were added to 300 g of ethanol, and stirred at 60° C. for 6 hours under a nitrogen atmosphere, with the stirring speed maintained at 300 rpm;
[0058] Add 5.2 g of silane coupling agent KH-550, and continue stirring at 45°C for 4 hours at a stirring speed of 300 rpm;
[0059] The mixture was cooled to room temperature, and then 21.5 g of nano-silicon dioxide, 320 g of water, 325 g of acrylic resin and 1280 g of ethanol were added and stirred to mix well.
[0060] Embodiment 2:
[0061] A preparation method of a hyperosmotic antifouling agent:
[0062] 10 g of glycidyl methacrylate, 19.3 g of 3-perfluorooctyl 2-hydroxypropyl acrylate, 8.4 g of trimethoxy (3,3,3-trifluoropropyl) silane, and 0.2 g of azobisisobutyronitrile were added to 300 g of ethanol, and stirred at 60° C. for 6 hours under a nitrogen atmosphere, with the stirring speed maintained at 300 rpm;
[0063] Add 5.2 g of silane coupling agent KH-550, and continue stirring at 45°C for 4 hours at a stirring speed of 300 rpm;
[0064] The mixture was cooled to room temperature, and then 21.5 g of nano-silicon dioxide, 320 g of water, 325 g of acrylic resin and 1280 g of ethanol were added and stirred to mix well.
[0065] Embodiment 3:
[0066] A preparation method of a hyperosmotic antifouling agent:
[0067] 10 g of glycidyl methacrylate, 19.3 g of 3-perfluorooctyl 2-hydroxypropyl acrylate, 4.2 g of 3,3,3-trifluoropropylmethyldimethoxysilane, 4.2 g of trimethoxy(3,3,3-trifluoropropyl)silane, and 0.2 g of azobisisobutyronitrile were added to 300 g of ethanol, and stirred at 60° C. for 6 hours under a nitrogen atmosphere, with the stirring speed maintained at 300 rpm;
[0068] Add 5.2 g of silane coupling agent KH-550, and continue stirring at 45°C for 4 hours at a stirring speed of 300 rpm;
[0069] The mixture was cooled to room temperature, and then 21.5 g of nano-silicon dioxide, 320 g of water, 325 g of acrylic resin and 1280 g of ethanol were added and stirred to mix well.
[0070] The preparation method of the hyperosmotic antifouling agent of the present invention comprises a variety of raw materials, which interact with each other during the reaction process to eventually form a coating with excellent waterproof performance. First, glycidyl methacrylate and 3-perfluorooctyl 2-hydroxypropyl acrylate are used as polymer monomers to participate in free radical polymerization to form a polymer network structure. Among them, glycidyl methacrylate, as a cross-linking agent, can react with other monomers to enhance the mechanical strength and water resistance of the polymer. 3-perfluorooctyl 2-hydroxypropyl acrylate not only has the basic structure of acrylate, but also contains a perfluorooctyl part, providing excellent hydrophobicity and oleophobicity, thereby significantly improving the waterproof performance of the coating. Fluoromethoxysilane compound trimethoxy (3,3,3-trifluoropropyl) silane and / or 3,3,3-trifluoropropyl methyl dimethoxy silane enhance the surface properties of the coating by providing a silane group, improve adhesion and chemical stability, and the introduction of trifluoropropyl increases the hydrophobicity of the coating. During the reaction, the initiator initiates a monomer polymerization reaction to promote polymer formation. In addition, the added silane coupling agent KH-550 reacts with the silane group to further enhance the adhesion and stability of the coating. Finally, nano-silica, acrylic resin and ethanol are added and mixed evenly to obtain a high-permeability antifouling agent. After being coated on the fabric, the coating formed by the antifouling agent has good waterproof properties, which are reflected in high contact angles and low rolling angles. This is due to the combined effect of the cross-linked structure formed by the raw materials during the reaction and the hydrophobic components, which enables the coating to effectively resist the penetration of moisture and pollutants, thereby maintaining the cleanliness and appearance of the surface.
[0071] Comparative Example 1:
[0072] A method for preparing a hyperosmotic antifouling agent:
[0073] 10 g of glycidyl methacrylate, 19.3 g of hydroxyethyl methacrylate, 8.4 g of 3,3,3-trifluoropropylmethyldimethoxysilane, and 0.2 g of azobisisobutyronitrile were added to 300 g of ethanol, and stirred at 60° C. for 6 hours under a nitrogen atmosphere, with the stirring speed maintained at 300 rpm;
[0074] Add 5.2 g of silane coupling agent KH-550, and continue stirring at 45°C for 4 hours at a stirring speed of 300 rpm;
[0075] The mixture was cooled to room temperature, and then 21.5 g of nano-silicon dioxide, 320 g of water, 325 g of acrylic resin and 1280 g of ethanol were added and stirred to mix well.
[0076] Comparative Example 2:
[0077] A preparation method of a hyperosmotic antifouling agent:
[0078] 10 g of glycidyl methacrylate, 19.3 g of 3-perfluorooctyl 2-hydroxypropyl acrylate, 8.4 g of γ-methacryloxypropyltrimethoxysilane, and 0.2 g of azobisisobutyronitrile were added to 300 g of ethanol, and stirred at 60° C. for 6 hours under a nitrogen atmosphere, with the stirring speed maintained at 300 rpm;
[0079] Add 5.2 g of silane coupling agent KH-550, and continue stirring at 45°C for 4 hours at a stirring speed of 300 rpm;
[0080] The mixture was cooled to room temperature, and then 21.5 g of nano-silicon dioxide, 320 g of water, 325 g of acrylic resin and 1280 g of ethanol were added and stirred to mix well.
[0081] Comparative Example 3:
[0082] A preparation method of a hyperosmotic antifouling agent:
[0083] 10 g of glycidyl methacrylate, 19.3 g of hydroxyethyl methacrylate, 8.4 g of γ-methacryloxypropyltrimethoxysilane, and 0.2 g of azobisisobutyronitrile were added to 300 g of ethanol, and stirred at 60° C. for 6 hours under a nitrogen atmosphere, with the stirring speed maintained at 300 rpm;
[0084] Add 5.2 g of silane coupling agent KH-550, and continue stirring at 45°C for 4 hours at a stirring speed of 300 rpm;
[0085] The mixture was cooled to room temperature, and then 21.5 g of nano-silicon dioxide, 320 g of water, 325 g of acrylic resin and 1280 g of ethanol were added and stirred to mix well.
[0086] Test Example 1:
[0087] The silk fabric is cleaned, dried, without coating and oil stain; the hyperosmotic antifouling agent prepared in the embodiment and the comparative example is evenly applied on the silk fabric by spraying, and the hyperosmotic antifouling agent is fully absorbed on the surface and left to stand for 20 minutes; the fabric coated with the hyperosmotic antifouling agent is naturally air-dried for 24 hours. The spraying amount of the hyperosmotic antifouling agent is 0.2 g of the hyperosmotic antifouling agent / 1 square centimeter of fabric.
[0088] Waterproof performance: The contact angle and rolling angle are measured according to the method in the national standard "GB / T 42694-2023".
[0089] Table 1 Test results of hyperosmotic antifouling agent
[0090] Contact angle / ° Roll angle / ° Example 1 123.2 39.3 Example 2 126.4 37.8 Example 3 136.5 24.4 Comparative Example 1 101.8 58.1 Comparative Example 2 107.2 52.5 Comparative Example 3 89.7 64.5
[0091] Experiments have shown that the synergistic effect of the fluoromethoxysilane compounds trimethoxy (3,3,3-trifluoropropyl) silane and 3,3,3-trifluoropropyl methyl dimethoxy silane in high permeability antifouling agents can significantly improve the waterproof performance. The mechanism of this synergistic effect is mainly reflected in their different structural characteristics and the cross-linked structure formed in the coating. The two fluoromethoxysilane compounds contain different fluorine groups and methoxy groups, which allow different types of cross-linked structures to be formed in the coating. The presence of the trifluoropropyl group helps to form a dense network structure because the fluorine group has strong hydrophobicity, which can promote the molecular arrangement to be more closely and increase the number of cross-linking points. At the same time, the methoxy group can enhance the adhesion of the coating because the methoxy group has good affinity and can form more chemical bonds with other groups, thereby enhancing the stability and firmness of the cross-linked structure. Such a cross-linked structure not only improves the durability and stability of the coating, but also effectively prevents the penetration of liquids, thereby improving the waterproof performance. Therefore, through the synergistic effect of trimethoxy (3,3,3-trifluoropropyl) silane and 3,3,3-trifluoropropylmethyldimethoxysilane, the cross-linking structure of the coating is enhanced, thereby significantly improving the waterproof performance of the high-penetration antifouling agent.
[0092] Test Example 2:
[0093] After further increasing the spraying amount on the basis of Test Example 1, when the amount of the hyperosmotic antifouling agent is 0.5 g of hyperosmotic antifouling agent / 1 square centimeter of fabric, the contact angle of Example 1 is 152.6°, the rolling angle is 13.7°, and it has more excellent anti-wetting performance.
[0094] Figure 1 This is a waterproof test diagram of Example 1 after applying the hyperosmotic antifouling agent (dosage: 0.5 g hyperosmotic antifouling agent / 1 cm2 of fabric) on dark fabric; Figure 2 This is a soy sauce proof test diagram of Example 1 after applying the hyperosmotic antifouling agent (dosage: 0.5 g hyperosmotic antifouling agent / 1 cm2 of fabric) on yellow fabric; Figure 3 This is a waterproof test diagram of Example 1 after applying the hyperosmotic antifouling agent (dosage: 0.5 g hyperosmotic antifouling agent / 1 cm2 of fabric) on the silk fabric; Figure 4 This is a waterproof test diagram of Example 1 after applying the hyperosmotic antifouling agent (dosage 0.5 g of hyperosmotic antifouling agent / 1 square centimeter of fabric) on the embroidered fabric; Figure 5 This is a waterproofing experiment diagram of Example 1 after applying the hypertonic antifouling agent (dosage 0.5 g of hypertonic antifouling agent / 1 square centimeter of fabric) on the intangible cultural heritage embroidery artwork. Figure 6 The left side of the pure cotton fabric was not treated and was absorbed by the fabric after pouring water; the right side of the pure cotton fabric was treated with a hyperosmotic antifouling agent (0.5 g of hyperosmotic antifouling agent / 1 square centimeter of fabric). After pouring water, it formed water droplets and was not absorbed by the fabric, with a significant waterproof effect.
[0095] The experimental results in Figures 1-6 show that when applied to fabrics of different colors and textures, the hyperosmotic antifouling agent effectively prevents the penetration of liquids such as water and soy sauce, forming a significant waterproof effect. This shows that after increasing the spraying amount, the hyperosmotic antifouling agent can stably form a coating with excellent waterproof performance in different scenarios, protecting the fabric from liquid pollution, showing high practical value and wide applicability.
[0096] The present invention can be used to protect non-legacy embroidery works, Hanfu fabrics, etc., as well as other special working scenes such as kitchens and other places that are prone to dirt. It is suitable for various fabrics, has simple operation, and has a powerful effect.
Claims
1. A hyperosmotic antifouling agent, characterized in that: Prepared by the following method: Glycidyl methacrylate, 3-perfluorooctyl 2-hydroxypropyl acrylate, fluoromethoxysilane compound, initiator, silane coupling agent KH-550 and ethanol are stirred; Then mix with nano-silica, water, acrylic resin and ethanol.
2. The hyperosmotic antifouling agent according to claim 1, characterized in that Prepared by the following method: Glycidyl methacrylate, 3-perfluorooctyl 2-hydroxypropyl acrylate, fluoromethoxysilane compound, azobisisobutyronitrile, silane coupling agent KH-550 and ethanol are stirred; Then mix with nano-silica, water, acrylic resin and ethanol.
3. The hyperosmotic antifouling agent according to claim 2, characterized in that Prepared by the following method: 5-15 parts by weight of glycidyl methacrylate, 10-30 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 5-12 parts by weight of fluoromethoxysilane compound, 0.05-0.9 parts by weight of azobisisobutyronitrile, 1-9 parts by weight of silane coupling agent KH-550 and 100-700 parts by weight of ethanol are stirred; The mixture is then mixed with 10-50 parts by weight of nano silicon dioxide, 100-500 parts by weight of water, 100-500 parts by weight of acrylic resin and 500-2000 parts by weight of ethanol.
4. The hyperosmotic antifouling agent according to claim 3, characterized in that: Prepared by the following method: 5-15 parts by weight of glycidyl methacrylate, 15-25 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 6-10 parts by weight of fluoromethoxysilane compound, 0.1-0.6 parts by weight of azobisisobutyronitrile, 3-7 parts by weight of silane coupling agent KH-550 and 100-500 parts by weight of ethanol are stirred; The mixture is then mixed with 15-35 parts by weight of nano silicon dioxide, 200-400 parts by weight of water, 200-400 parts by weight of acrylic resin and 800-1400 parts by weight of ethanol.
5. The hyperosmotic antifouling agent according to claim 4, characterized in that: Prepared by the following method: Add 5-15 parts by weight of glycidyl methacrylate, 15-25 parts by weight of 3-perfluorooctyl 2-hydroxypropyl acrylate, 6-10 parts by weight of fluoromethoxysilane compound, and 0.1-0.6 parts by weight of azobisisobutyronitrile to 100-500 parts by weight of ethanol, and stir at 55-70° C. for 4-8 hours at a stirring speed of 100-500 rpm under a nitrogen atmosphere; Add 3-7 parts by weight of silane coupling agent KH-550, continue stirring at 35-50°C for 2-6 hours, and the stirring speed is 100-500rpm; The mixture is cooled to room temperature, and then 15-35 parts by weight of nano-silicon dioxide, 200-400 parts by weight of water, 200-400 parts by weight of acrylic resin and 800-1400 parts by weight of ethanol are added, and the mixture is stirred and mixed evenly.
6. Use of the hyperosmotic antifouling agent as described in any one of claims 1 to 5 in fabrics for waterproofing, antifouling and oil resistance.
7. The use of the hyperosmotic antifouling agent in fabrics for waterproofing, antifouling and oil resistance as claimed in claim 6, characterized in that: The fabric is silk fabric, embroidery fabric, cotton fabric, polyester fabric, nylon fabric, flannel or chiffon fabric.
8. The use of the hyperosmotic antifouling agent in fabrics for waterproofing, antifouling and oil resistance as claimed in claim 7, characterized in that: The fabric is silk fabric or embroidery fabric.
9. The use of the hyperosmotic antifouling agent in fabrics for waterproofing, antifouling and oil resistance as claimed in claim 6, characterized in that: The method comprises uniformly coating the high permeability antifouling agent described in any one of claims 1 to 5 on the fabric by spraying or coating.